2009
DOI: 10.1016/j.enggeo.2008.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical investigation of a large landslide in glaciolacustrine clays in the Trièves area (French Alps)

Abstract: Slope movements in clay deposits are world widespread and result from complex deformation processes, including internal strains in the landslide body and slipping along rupture surfaces. Such mass movements are likely to generate changes in the geophysical parameters characterizing the ground, which can be used to map the landslide body. In the last decade, geophysical techniques have been increasingly used for landslide investigation purposes. However, the success of any geophysical technique is overall contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
89
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 31 publications
5
89
0
1
Order By: Relevance
“…This reduced 193 the acquisition time as only one source type was required, and also ensured the same source 194 location and signature for both P-and S-wave SRT. This is in contrast to many other studies that are 195 using distinct P-and SH-wave data acquisitions (e.g., Jongmans et al, 2009;Turesson, 2007). 196…”
mentioning
confidence: 80%
“…This reduced 193 the acquisition time as only one source type was required, and also ensured the same source 194 location and signature for both P-and S-wave SRT. This is in contrast to many other studies that are 195 using distinct P-and SH-wave data acquisitions (e.g., Jongmans et al, 2009;Turesson, 2007). 196…”
mentioning
confidence: 80%
“…Likewise, due to wireless data transmission, these units can serve as valuable low-cost tools for monitoring environmental phenomena and are particularly suited for landslide monitoring, since they allow repeated images of the S-wave velocity model. With regards to this, Jongmans et al (2009) have shown that S-wave velocity is very sensitive to clay consolidation (and the corresponding decrease in porosity) and should tend to zero in the event of liquefaction. Also, a significant drop in v s of around 10 % was measured at the base of a small active landslide several days before its failure (Mainsant et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Jongmans et al (2009) showed a clear correlation between surficial displacement rates (related to clay deformation) and S-wave velocity changes (obtained by active seismic refraction) on a landslide in the French Alps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At least 15 % of the area covered by the varved clays is considered to be unstable (Jongmans et al, 2009). Displacement velocities range from several millimeters to several centimeters per year, with the risk that the velocities may suddenly increase and lead to catastrophic failure.…”
Section: Introductionmentioning
confidence: 99%